Kepuasan Pengguna Jasa Terminal Angkutan Umum di Bangka Selatan - Sari Apriliani; Prasadja Ricardianto; Siska Amonalisa; Sri Handayani; Yana Tatiana (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
Toboali Public Transportation Terminal is one of the most important terminals in South Bangka Regency due to the route access of public transportation in Toboali as the capital of Bangka- Belitung Province. Each public transport to Sadai Port area and to Pangkal Pinang City will go through this terminal. The purpose of the study is to determine and analyze the level of service quality toward the users satisfaction at Toboali Terminal in South Bangka Regency. There are some main problems which are; the traffic flow continues to become denser, some terminal facilities are inadequate, the schedule of public transportation arrival in the terminal is not precise, the late response to terminal internal condition, and lame security condition in the terminal. The sample used in this study was 50 respondents. The data analysis technique used Customer Satisfaction Index method which aims to determine the level of service users satisfaction. Based on the calculation of Customer Satisfaction Index, the results obtained in the form of the level of service users satisfaction with the quality of Toboali Terminal services. The level of passenger respondents satisfaction is 67% where the value is in range of 0.66-0.80. It means that overall passenger respondents are satisfied. Reliability is the dimension of the highest level of satisfaction with the quality of service at Toboali Terminal.